Processos de aprendizagem e suas influências sobre a acumulação de competência tecnológica : o caso da Empresa Enxuta Industrial Ltda. - Fenner, Adelar Carlos (2001)
This dissertation 1S a study on technological learning take for empirical evidences described in the chapter VI accordingly to the table 3.1. Searching to identify ENXUT A's evolution of the accumulation trajectory on technological competencies during the studied period 1980-2000 for technological functions of investment (decisions and control over plan and engineering projects), process and production organizations, products and equipment as well. To produce structures of technological competencies for home appliances industries, was utilized Figueredo's (2000) analytical frameworks. On the other hand regarding the empirical evidences described in chapter VII, accordingly to the table 3.2., was searched to spot the intluence of the learning process used by the Company on the evolution of the accumulation trajectory of technological competencies. The Leaming Process are evaluated accordingly to the four main characteristics: variety, intensity, working operation and interaction used from Figueredo's (2000) development structures. This study verified the way and speed accumulation of technological competencies at ENXUT A INDUSTRIAL L TDA were intluenced by leaming processes and mechanism used to acquire technological knowledge and to tum it into an organizational manner. This processes and learning mechanism permitted the Enterprise to reach higher speed of accumulation technological capacities when entered in the home appliances industry which proportioned to reach the necessary technological development in order to work in this industrial area. Nevertheless, the simple incidence ofthose processes in the company didn't guarantee a positive implication for the accumulation of technological competence. Because from the period 1991 to 1995 was proved true the functional deterioration of such leaming processes used in the company, which could have intluenced negatively the repeatability and the interaction of those processes. This seems to have contributed in such way and the Enterprise couldn't structure neither accumulate or renew technological competencies in that period. Through the use of existent structure in the literature, applied to an industry different from previous studies, this essay suggests that an organized, continuous and integrated effort should exist for generation and knowledge dissemination in the company, in which the accumulation of technological competencies can be accelerated in such way to let the enterprise to structure a trajectory closer to the boundary industry's technological development.